Upaya Guru Tahfidz dalam Meningkatkan Kemampuan Menghafal Al-Qur’an Siswa Kelas X di Madrasah Aliyah Pusat Menes - Adelia Putri; Bunyamin (Attractive : Innovative Education Journal, 2024)
The purpose of this investigation is 1) to determine the efforts of tahfidz teachers in increasing their Al-Qur'an memorization skills. 2) to determine the supporting and inhibiting factors that tahfidz teachers have in increasing their Al-Qur'an memorization skills with class X students at Menes Central Madrasah Aliyah.  This investigation applies a descriptive qualitative approach in the type of case study. The results of the investigation regarding the tahfidz teacher's efforts to improve the ability to memorize the Al-Qur'an for class X students at the Menes Central Madrasah Aliyah are: 1) cooperation between tahfidz teachers and parents through personal communication, providing motivation to students, giving memorization targets to students, guiding students to continue muroja'ah, using talqqi and bin nazhar methods. The supporting factors in increasing students' Qur'an memorization, namely: 2) Conducive classroom atmosphere, classical learning system, Al-Qur'an mushaf facilities that are memorized for free, and listening to Al-quran murottal every morning. The inhibiting factors include: The temptation of social media and gadgets, students' lack of understanding of tajweed and the correct pronunciation of makhorijul huruf, students' changing conditions such as laziness to memorize, and limited time, which is only 3 lesson hours.